Effects of single and combined inoculation of plant growth promoting rhizobacteria on growth performance of paddy (Oryza sativa L.) under glasshouse and field conditions - A Razak, Mohamad Halid (2018)
Rice (Oryza sativa L.) is a staple food in Malaysia grown over 708,148 hectares in various granary areas of Malaysia. In 2016, the average rice production in Malaysia was 2.252 million tons. As the population of Malaysia increases from the current number of 31.2 million, the rice demand also increases. However, Malaysia is only able to achieve 71.2% self-sufficiency level (SSL). Thus, Malaysia has to import rice from other countries, requiring higher productivity in limited granary areas to fulfill domestic demand. A potential solution to this problem is by increasing the usage of plant growth promoting rhizobacteria (PGPR) as a biofertilizer to enhance the productivity and reduced environmental problems caused by application of chemical fertilizers. The objectives of this study were to study the interaction effects of single and combined inoculations of PGPR using in vitro assay studies, effects on rice growth and development in glasshouse experiments and effects on rice yield, biomass and nutrient uptake in a field experiment. Determination of panicle breaking strength to minimize panicle grain shattering under field experiments was also conducted in this study. PGPR used in this study were Bacillus pumilus GM118 and Bacillus subtillis UPMB10 which act as phosphate solubilizing bacteria (PSB) and nitrogen fixing bacteria (NFB), respectively. B. pumilus GM118 and B. subtillis UPMB10 growth population trends, ability to fix nitrogen and solubilize phosphate on three different selective media and production of indole-3-acetic acid (IAA) were conducted in vitro assay. Four treatments of PGPR with different fertilizers treatments (including control) were laid out in a randomized complete block design (RCBD) with four replications conducted in a glasshouse at Ladang 10, Faculty of Agriculture, Universiti Putra Malaysia. The treatments were as follows: T1: control N0K0; T2: N0K90; T3: N40K30; T4: N40K60; T5: N80K30; T6: N80K60; T7: N120K0 and T8: N120K90 in the present/absent of single and combined inoculations of B. pumilus GM118 and B. subtilis UPMB10. N and K in the treatments refer to the amount of nitrogen and potassium, respectively. The paddy variety used in glasshouse experiment was MR263 and it was planted using 35 L buckets containing 15 kg of paddy soil. Meanwhile, the field experiment was conducted in Kemasin-Semerak Integrated Agricultural Development Area (IADA), Kelantan. Four treatments were applied in IADA Kemasin-Semerak: T1: control (without bacterial inoculation); T2: single inoculation of B. pumilus GM118; T3: single inoculation of B. subtilis UPMB10 and T4: combined inoculations of B. pumilus GM118 and B. subtilis UPMB10. Normal fertilization practices were used in these plots. All data were analyzed statistically using SAS Software Program (Version 9.3) and treatment means were compared using Duncan Multiple Range Test (P < 0.05). In vitro assay indicated that combined inoculations of B. pumilus GM118 and B. subtilis UPMB10 produced the shortest generation times (14.4 minutes) for cells doubling compared to single inoculations of B. pumilus GM118 (36.1 minutes) and B. subtilis UPMB10 (24.1 minutes). However, single inoculation of B. subtilis UPMB10 is able to produce more IAA (63.8 μg/mL) compared to combined inoculations of B. pumilus GM118 and B. subtilis UPMB10 (50.1 μg/mL). Combined inoculations of B. pumilus GM118 and B. subtilis UPMB10 produced the highest grain yield (33%), followed by single inoculations of B. subtilis UPMB10 (29%) and B. pumilus GM118 (23%) as compared to the control in the glasshouse experiment. B. pumilus GM118 showed the highest N contents (15%) while combined inoculations of B. pumilus GM118 and B. subtilis UPMB10 showed the highest K content (16%) compared to control. Detachment of the grain panicle from the pedicle required the highest force for paddy inoculated with single inoculation of B. subtilis UPMB10 (11%) and followed by combined inoculations of B. pumilus GM118 and B. subtilis UPMB10 (8%) as compared to the control. In the field experiment, both single and combined inoculations of B. pumilus GM118 and B. subtilis UPMB10 showed significant difference in grain yield and biomass. In grain yield, B. pumilus GM118 produced 40%, B. subtilis UPMB10 (61%) and combined inoculations (61%) higher compared to the control. For biomass production, B. pumilus GM118 produced 33%, B. subtilis UPMB10 (42%) and combined inoculations of both (40%) higher compared to the control. IADA Kemasin-Semerak study showed that single inoculation of B. pumilus GM118 was able to increase 44% and 126% of plant N and P uptake while B. subtilis UPMB10 was able to increase 30% of plant K uptake compared to control, respectively. This study indicated that co-inoculation having beneficial multi-mechanism of fixing nitrogen, solubilizing phosphate and producing IAA, gave the optimum performance in both glasshouse and field studies. This study proves that inoculation of selected PGPR can enhance rice plant yield, biomass, nutrient uptake and reduce postharvest losses due to grain shattering. The results showed the potential use of combined inoculations of B. pumilus GM118 and B. subtilis UPMB10 as biofertilizer with multiple beneficial characteristics that can increase rice productivity in the granary areas of Malaysia.